(untitled) (Research, Society and Development, 2021)
The historical trajectory of teaching in Accounting Sciences, Economic Sciences and Administration in Brazil takes us back to the beginnings of Commercial Education in the country, which was the historical predecessor of the three courses mentioned. In this perspective, the purpose of this article is to present the origin and history of Business Education, so that we can better understand the process of (trans)formation of Business Education and its relationship with the emergence of higher education courses in Accounting, Economics and Administration throughout of the 20th century. Therefore, we will show the origin and the most relevant events of Commercial Education in the following periods: a) Empire Brazil b) first period of the Vargas Era, c) Dictatorial Government of Getúlio Vargas, also known as Estado Novo and d) redemocratization of Brazil, also known as the Second Republic. As methodological aspects, this research is classified in relation to its nature as basic; qualitative approach. Regarding the objectives, it is descriptive and the technical procedure used was bibliographical and documentary research. In the results of this bibliographical review, we present the relevance of understanding the history of courses and school subjects, in particular, Commercial Education, in its historical processes of genesis, consolidation and insertion in the history of school institutions.